2019
DOI: 10.1111/bcp.13861
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals' attitudes towards deprescribing in older patients with limited life expectancy: A systematic review

Abstract: Aims:The aim of this systematic review was to explore health care professionals' attitudes towards deprescribing in older people with limited life expectancy. Methods:A systematic literature search was conducted from inception to December 2017 using MEDLINE, EMBASE and CINAHL. Studies were included if they specifically concerned older people (≥65 years) with limited life expectancy, including those residing in any type of aged care facility, or were based on representative patient profiles. Results were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 90 publications
0
36
1
Order By: Relevance
“…Healthcare professionals have reported the same concerns in other studies [35], stressing the importance of interprofessional teams for successful deprescribing, and the frequent time constraints imposed by under-staffing and the high administrative load.…”
Section: Healthcare System: Coherent and Stable Healthcare Teams Paidmentioning
confidence: 53%
See 1 more Smart Citation
“…Healthcare professionals have reported the same concerns in other studies [35], stressing the importance of interprofessional teams for successful deprescribing, and the frequent time constraints imposed by under-staffing and the high administrative load.…”
Section: Healthcare System: Coherent and Stable Healthcare Teams Paidmentioning
confidence: 53%
“…Similarly, the fact raised by physicians that they do not feel comfortable adapting prescriptions made by colleagues, appears counterproductive. These territorial boundaries are the result of strong professional cultures, which are difficult to change as a whole; they seem not to be specific to Switzerland, as physicians in other settings reported the same hesitancy to address drugs prescribed by a colleague [35]. However, the development of collaborations in a network of stable external partners regularly mobilised by the NH team (that goes from the general practitioner to specialists and even to the surrounding hospitals) could contribute to optimise drug consumption.…”
Section: Institutional Level: Finding Time and Improving Interprofessmentioning
confidence: 99%
“…The factors which influence effective clinical decision-making in the frail elderly are crystallizing. Lundby et al (71) identified four themes related to health care professionals' attitudes towards de-prescribing in older people with limited life expectancy: patient and relative involvement, the importance of teamwork, health care professionals' self-assurance and skills, and the impact of organizational factors. There is a sea change in patients' attitudes as well.…”
Section: Moving Forward: Overcoming the Barriersmentioning
confidence: 99%
“…All interviews were conducted with one author as moderator (CL) and observer (TG or DN), respectively. The interviews followed an interview guide which was developed based on previous literature (Anderson et al, 2014;Bokhof & Junius-Walker, 2016;Lundby et al, 2019), comprising five main topics: 1) the patient population, 2) the HCPs' daily work, 3) the HCPs' collaboration with other HCPs, 4) the use of clinical treatment guidelines, and 5) the process of stopping a medication. In the beginning of each interview, a thorough introduction to the patient population, i.e., older patients with limited life expectancy (defined as an expected life expectancy of 1-2 years), was given to the participants.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…A recent systematic review of qualitative studies have explored HCPs' attitudes towards deprescribing specifically in older patients with limited life expectancy (Lundby et al, 2019). However, the studies included in this review mainly concern the perspectives of primary care physicians.…”
Section: Introductionmentioning
confidence: 99%